The Value of Independent Specialty Designation for Interventional Cardiology. DOI: 10.1002/ccd.26656 - James C. Blankenship; Wayne A. Powell; Dawn R. Gray; Peter L. Duffy (Catheterization and Cardiovascular Interventions, 2017)
BACKGROUND: In small, tortuous coronary lesions, the long-term comparative performance of drug-coated balloon (DCB) angioplasty versus drug-eluting stent (DES) treatment remains uncertain, despite both strategies being widely used in contemporary percutaneous coronary intervention (PCI) practice. AIMS: This study aimed to compare 3-year clinical outcomes between DES and DCB in patients undergoing PCI for small, tortuous coronary lesions. METHODS: This retrospective, single-center study included 366 patients treated with either DES (n = 226) or DCB (n = 140) for lesions with at least one angulation ≥ 45°. The primary endpoint was major adverse cardiac events (MACE). Time-to-event outcomes were assessed using Kaplan-Meier analysis and Cox proportional hazards models. RESULTS: Procedural success rates were high and comparable between groups. At 3 years, MACE occurred more frequently in the DCB group than in the DES group (log-rank p = 0.013). In multivariable analysis, DCB use remained associated with higher risks of MACE (hazard ratio [HR] 1.88; 95% confidence interval [CI] 1.12-3.16; p = 0.017) and target vessel revascularization (TVR) (HR 1.84; 95% CI 1.01-3.21; p = 0.045). Subgroup analysis showed that DES had significantly better outcomes than DCB in lesions with mild-to-moderate tortuosity, whereas event rates were similar between groups in severely tortuous segments. CONCLUSION: In small, tortuous coronary lesions, DES use was associated with lower rates of MACE and TVR at 3 years than DCB use. The advantage of DES was most apparent in mild-to-moderate tortuosity, whereas it was not statistically significant in severely tortuous vessels. These findings highlight the importance of anatomic complexity when selecting a treatment strategy for tortuous coronary lesions.